Preliminary Assessment of Secondary Metabolites of Selected Pteridophytes from Jorhat, Assam, India: Phytochemical Profiling of Assam Pteridophytes - HANDIQUE , Liza; BORAH, Baishali; UPADHYAY , Amit; AZAD, Mirzana (Journal of Tropical Biology & Conservation (JTBC), 2025)
This study analyses the phytochemical constituents of seven pteridophytic species from Assam, India. The methanolic extracts of seven species: Pyrrosia lanceolata, Pyrrosia nummularifolia, Ampheneuron opulentum, Sphenomeris chinensis, Selaginella sp., Diplazium esculentum, and Blechnum orientale were screened for phenolic, flavonoid, and flavonol content using standard spectrophotometric methods. Pyrrosia nummularifolia exhibited the highest flavonoid content, while Diplazium esculentum had the highest flavonol concentration. These bioactive compounds, known for their antimicrobial, antioxidant, and anti-inflammatory properties, support their traditional medicinal use and highlight their potential for drug discovery. Further studies are required to isolate and identify the pharmacologically active compounds from these species.